Analysis of The Role of Motivation in The Relationship Between Transformational Leadership and Islamic Work Ethics in Increasing Employee Productivity - Didin, Didin; Dudung Hadiwijaya; Priyo Susilo (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
This takes a look at a quantitative narrative version of the use of field records to check examples of transformational management and Islamic paintings ethics on worker productivity with motivation as an intervening variable. The studies populace is Kopsha Rabbani personnel. The pattern accumulated amounted to 145 human beings using the random sampling approach and the use of the Slovin device. The research was processed using the WarpPLS eight.0 software. Specific checks display that transformational management does not affect motivation, Islamic painting ethics affects motivation, transformational leadership has an impact on worker productivity, and Islamic paintings ethics has no impact on employee productivity. Motivation is established to affect motivation. Worker. Worker productivity. The impersonal takeaway is that transformational management does not propose employee productivity through motivation, and the Islamic work ethic influences worker productiveness through motivation. In the improvement of human resources (SDI), it is vital to instil Islamic painting ethics systematically to encourage and inspire personnel to grow their productivity.